2004
DOI: 10.1002/ijc.20512
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of TGF‐β1 and PAI‐1 in cervical cancer

Abstract: Cervical carcinoma is a human papilloma virus (HPV)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 61 publications
1
40
0
1
Order By: Relevance
“…Multivariate analysis indicated that only plasma TGF-ß1 levels were an independent and significant prognostic factor of disease-free survival, associated with increased risk of poor prognosis. Both TGF-ß1 and Endoglin act as valuable indicators of prognosis in several tumors (56,70,(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis indicated that only plasma TGF-ß1 levels were an independent and significant prognostic factor of disease-free survival, associated with increased risk of poor prognosis. Both TGF-ß1 and Endoglin act as valuable indicators of prognosis in several tumors (56,70,(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97).…”
Section: Discussionmentioning
confidence: 99%
“…To explore the role of TGF-b in the generation of CD105-positive vessels both the presence of CD105-positive blood vessels in the epithelial cell clusters and the number of blood vessels in the stroma were associated with the presence of PAI-1 in the epithelial cell clusters (Hazelbag et al, 2004) and the amount of fibronectin in the stroma (Hazelbag et al, 2002), both target genes of TGF-b 1 .…”
Section: Association Between Blood Vessels and Tumour-associated Macrmentioning
confidence: 99%
“…Furthermore, TGF-b 1 is known to induce VEGF expression (McMahon et al, 2006). Earlier we have reported on the expression of TGF-b 1 , plasminogen activator inhibitor (PAI)-1 and fibronectin (both target gene products of TGF-b 1 ) and avb6 (activator of TGF-b 1 ) in cervical carcinoma (Hazelbag et al, 2002(Hazelbag et al, , 2004(Hazelbag et al, , 2007.…”
mentioning
confidence: 99%
“…35 TGF-β is another cytokine that inhibits activation, proliferation, and activity of lymphocytes. 36 This cytokine is also found in high concentration in cancer patients and is associated with tumor progression, 37 poor prognosis, 38 and lack of response to immunotherapy. 39 TGF-β can induce the production of IL-10 that leads to suppression of the immune response to cancer cells.…”
Section: Role Of Immunosuppressive Mediators and Tumor-associated Macmentioning
confidence: 99%